Unknown soldier - Oberle, Isabell; Schubert, Stefan (2024)
Abstract: As the epitome of commitment and willingness to make sacrifices, the allegorical figure of the Unknown Soldier became the focal point of national memory in the period between the World Wars. The figure represented an idealised, collective and heroic imagining of the ordinary soldier who had lost his life for his fatherland. The figure of the Unknown Soldier contributed to the perpetuation of a certain type of soldier hero in the modern era and simultaneously served both the coalescence of national mourning and the retrospective legitimisation of the sacrifices made during the First World War